A Minimalist Single‐Layer Metasurface for Arbitrary and Full Control of Vector Vortex Beams. Issue 6 (23rd December 2019) - Bao, Yanjun; Ni, Jincheng; Qiu, Cheng‐Wei
Abstract: Vector vortex beams (VVBs) possess ubiquitous applications from particle trapping to quantum information. Recently, the bulky optical devices for generating VVBs have been miniaturized by using metasurfaces. Nevertheless, it is quite challenging for the metasurface‐generated VVBs to possess arbitrary polarization and phase distributions. More critical is that the VVBs' annular intensity profiles demonstrated hitherto are dependent on topological charges and are hence not perfect, posing difficulties in spatially shared co‐propagation of multiple vortex beams. Here, a single‐layer metasurface to address all those aforementioned challenges in one go is proposed, which consists of two identical crystal‐silicon nanoblocks with varying positions and rotation angles (i.e., four geometric parameters throughout). Those four geometric parameters are found to be adequate for independent and arbitrary control of the amplitude, phase, and polarization of light. Perfect VVBs with arbitrary polarization and phase distributions are successfully generated, and the constant intensity profiles independent of their topological charges and polarization orders are demonstrated. The proposed strategy casts a distinct perception that a minimalist design of just one single‐layer metasurface can empower such robust and versatile control of VVBs. That provides promising opportunities for generating more complex vortex field for advanced applications in structural light, optical micromanipulation, and data communication. Abstract : A single‐layer dielectric metasurface, consisting of two crystal‐silicon nanoblocks within one unit, is proposed to control the amplitude, phase, and polarization of light independently and arbitrarily. A genetic algorithm is used to obtain the geometric parameters of the metasurface element. The proposed strategy enables perfect vector vortex beam generation with constant annular intensity profiles, arbitrary phase, and polarization distributions.